0517 Management Of Sleep Apnea Patients By A Clinical Nurse: A Randomized Open-label Non-inferiority study. (12th April 2019) - Lajoie, Annie C; Privé, Alexis; Roy-Hallé, Annie; Series, Frederic
Abstract: Introduction: Obstructive sleep apnea (OSA) is a prevalent disease and references for the evaluation of patients with suspected OSA often exceeds the sleep clinic's evaluation capacity thus creating important delays in patients' care. Methods: We performed a randomized open-label non-inferiority study. Patients who were referred to our sleep clinic and had a cardiopulmonary report suggestive of OSA (apnea-hypopnea index greater than 20 events per hour) were randomized to a nursed based or a physician based initial evaluation. Statistical analyses are available for the outcomes at 3 months. The primary endpoint, change in Epworth Sleepiness Scale (ESS) and quality of life (Quebec Quality of Life Questionnaire) from baseline and secondary endpoints of treatment adherence, were assessed using ANOVA. Results: 200 patients were randomized; patient characteristics and choice of therapy were similar between groups. Overall 79, 5 % were prescribe continuous positive airway pressure (CPAP) therapy, 3% mandibular advancement device (MAD), 6, 5 % upper airway surgery, 1% weight reduction, 2 % positional therapy and 8% refused treatment. At 3 months, patients with CPAP therapy in the nursed-based versus physician-based evaluation had comparable parameters (90 th percentile pressure 8.7 versus 8.0 cmH2 O, p=0.27 and mean pressure (2.0 versus 6.6 cmH2 O, p=0.36) and adherence [371 versus 386 min per night (mean difference 14.2 min; p=0.42) and 74.6 versus 81.3 percent of nights with usage exceeding 4 hours, p=0.14]. There was no significant change in the ESS or any of the domains of the Quebec Quality of Life Questionnaire from baseline in both groups at 3 months. Conclusion: We found no difference between a nurse-based and physician-based initial evaluation at the sleep clinic at 3 months. Data at 6 months will likely confirm non-inferiority of this approach. Support (If Any): This study was supported by the Sleep Apnea Research and Teaching Fund of the IUCPQ-UL Foundation and the Alphonse L'Espérance Funds.